A REVIEW OF LITERATURE ON RESEARCH IN SCIENCE EDUCATION IN INDIA - Thokchom , Monica Devi; Koijam, Sobita Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Research in Science education helps in identifying the current knowledge and trends of how teaching and learning in science is taking place at all school levels. It also helps in improving instructional practice in schools and teacher education. This paper present the literature review of journal published in the Journal of India Education, Indian Educational Review, Indian Journal of Educational Technology & Voices of Teachers and Teacher Educators. It highlight the low trend in research in science education so an effective planning is requires to boost science education.